2019
DOI: 10.1016/j.isci.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Dependent Umpolung Reactivity of Carbenes Derived from Cyclopropenes

Abstract: Summary Metal carbenes, divalent carbon species, are versatile intermediates that enable novel synthetic pathways. These species exhibit either electrophilic or nucleophilic character, depending on the carbene and metal fragments. Although the metal carbene reactivity is regulated by the metal, the umpolung of carbene reactivity by changing metal remains challenging. Here, we report a unique metal-induced de novo umpolung of carbene reactivity, wherein a carbene precursor can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Recently, we uncovered a unique reaction of cyclopropene alcohols with isatins, in which the oxonium ylides from cyclopropene alcohols were captured as reactive ketones at the vinylogous site (Scheme 1b). 25 This seminal discovery demonstrated that cyclopropene, a versatile precursor of donor-type vinyl carbenes, could be applied to ylide-trapping chemistry. Inspired by this study and the transition-metal-catalyzed cycloisomerization of cyclopropene carboxylic acids by Komendantov and Dominin, 26 we anticipated that the we could employ the stable, readily available cyclopropene carboxylic acids 27 to serve as new types of precursors of cyclic carboxylic oxonium ylides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we uncovered a unique reaction of cyclopropene alcohols with isatins, in which the oxonium ylides from cyclopropene alcohols were captured as reactive ketones at the vinylogous site (Scheme 1b). 25 This seminal discovery demonstrated that cyclopropene, a versatile precursor of donor-type vinyl carbenes, could be applied to ylide-trapping chemistry. Inspired by this study and the transition-metal-catalyzed cycloisomerization of cyclopropene carboxylic acids by Komendantov and Dominin, 26 we anticipated that the we could employ the stable, readily available cyclopropene carboxylic acids 27 to serve as new types of precursors of cyclic carboxylic oxonium ylides.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of 2a with 8-hydroxyquinoline, PPh 3 , and pyridine N -oxide indicate the pronounced electrophilicity and lability of the rhodium-carbon bonds in rhodapentalenes and are consistent with the chemical behavior of rhodium carbene moieties (Berry, 2012, Tindall et al., 2018, Zhang et al., 2019). The steric crowding of the bulky phosphonium group adjacent to the C1-position may account for the C7-position being the sole active site in the reactions of 2a .…”
Section: Resultsmentioning
confidence: 55%
“…Cluster 3 , unlike most organometallic carbenes, [25–29] is stable in the solution up to ∼100 °C suggesting an idea that the Os−C carbene binding energy in 3 is unusually high. This assumption is confirmed by the fact that the attempt to replace the carbene ligand with PPh 3 in cluster 3 leads to substitution of one CO group instead.…”
Section: Resultsmentioning
confidence: 99%